The impact of cash financing on housing prices: a theoretical framework and empirical evidence from a volatile United States market cycle. Issue 1 (2nd January 2023) - Aroul, Ramya R.; Hansz, J. Andrew
ABSTRACT: This study examines cash financing transaction price implications over a 12-year United States (U.S.) housing market cycle centred around the 2008 Housing Crisis, a period of unprecedented transaction price volatility. We establish theoretical reasoning and empirical confirmation of the mortgage contingency pricing effect, operationalised as a cash financing discount. We document that cash discounts are associated with market conditions, price levels, and improvement sizes and conditions. Larger empirical cash discounts are related to greater market distress, lower price levels, smaller improvement sizes, and inferior improvement conditions. We conclude that a one-size-fits-all rule-of-thumb is not appropriate when estimating cash financing pricing impacts. Finally, additional research is encouraged across different market conditions and in non-U.S. markets.